Policies with Respect to Foreign Investors in the New Member States of the European Union and in the Developing Countries of Asia: A Comparative Aspects - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2009)
The purpose of this article is to provide a comparative analysis of policies aimed at foreign investors in the new member states of the European Union as well as in the developing countries of Asia. The policies demonstrate certain similarities in spite of the fact that the analyzed world economic regions are subject to different conditions. A common feature is the opening up of economies to foreign investors, coupled with the application of certain incentives intended to increase the attractiveness of the country to foreign investors. Countries strive to modernize their economies with the help of foreign capital. The developing countries of Asia, in contrast to the new member states of the European Union, are not restricted in their policies with respect to foreign investors by the requirements of regional economic integration.
Keywords: 330